A Mobile Phone App for the Generation and Characterization of Motor Habits - Banca, Paula; McNamee, Daniel; Piercy, Thomas; Luo, Qiang; Robbins, Trevor W. (Frontiers in Psychology, 2020)
Habits are a powerful route to efficiency; the ability to constantly shift between goal-directed and habitual strategies, as well as integrate them into behavioral output, is key to optimal performance in everyday life. When such ability is impaired, it may lead to loss of control and to compulsive behavior. Habits have successfully been induced and investigated in rats using methods such as overtraining stimulus–response associations and outcome devaluation, respectively. However, such methods have ineffectively measured habits in humans because 1) human habits usually involve more complex sequences of actions than in rats; 2) of pragmatic impediments posed by the extensive time (weeks, or even months), it may take for routine habits to develop. We present here a novel behavioral paradigm - a mobile-phone app methodology - for inducing and measuring habits in humans during their everyday schedule and environment. It assumes that practice is key to achieve automaticity and proficiency, and that the use of a hierarchical sequence of actions is the best strategy for capturing the cognitive mechanisms involved in habit formation (including 'chunking') and consolidation. The task is a gamified self-instructed and self-paced app on a mobile phone that enables subjects to learn and practice two sequences of finger movements, composed of chords and single presses. It involves a step-wise learning procedure in which subjects begin responding to a visual and auditory cued sequence by generating responses on the screen using four fingers. Such cues progressively disappear throughout one month of training, enabling the subject ultimately to master the motor skill involved. We present preliminary data for the acquisition of motor sequence learning in 29 healthy individuals, each trained over a month period. We demonstrate an asymptotic improvement in performance, as well as its automatic nature. We also report how people integrate the task into their daily routine, the development of motor precision throughout training and the effect of intermittent reinforcement and reward extinction in habit preservation. The findings help to validate this ‘real world’ app for measuring human habits.